2016
DOI: 10.4292/wjgpt.v7.i3.440
|View full text |Cite
|
Sign up to set email alerts
|

Increase in colonic diverticular hemorrhage and confounding factors

Abstract: AIM:To classify changes over time in causes of lower gastrointestinal bleeding (LGIB) and to identify factors associated with changes in the incidence and characteristics of diverticular hemorrhage (DH). METHODS:A total of 1803 patients underwent colonoscopy for overt LGIB at our hospital from 1995 to 2013. Patients were divided into an early group (EG, 1995(EG, -2006 n = 828) and a late group (LG, 2007(LG, -2013 Author contributions: Kinjo K collected and analyzed the data, and drafted the manuscript; Mats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…The proportion of diverticular bleeding was increasing significantly from 1.02% (22 of 2,157 subjects) in 2003 to 1.67% (69 of 4,159 subjects) in 2011, and it was associated with an increased number of patients aged 40-59 years. Kinjo et al [49] also reported that patients with colonic diverticular bleeding were older male patients (≥70 years old) and that colonic diverticular bleeding was more frequent in the late-period group (2007-2013) than in the early-period group (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006).…”
Section: Diverticular Bleedingmentioning
confidence: 99%
“…The proportion of diverticular bleeding was increasing significantly from 1.02% (22 of 2,157 subjects) in 2003 to 1.67% (69 of 4,159 subjects) in 2011, and it was associated with an increased number of patients aged 40-59 years. Kinjo et al [49] also reported that patients with colonic diverticular bleeding were older male patients (≥70 years old) and that colonic diverticular bleeding was more frequent in the late-period group (2007-2013) than in the early-period group (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006).…”
Section: Diverticular Bleedingmentioning
confidence: 99%
“…The cases of colonic diverticular bleeding are increasing in relation to the rising incidence of colonic diverticulosis and antithrombotic drug use. [ 7 ] Although the mechanism of colonic diverticular bleeding is not fully understood, it is thought to be caused by a rupture of the vasa rectum at the neck or dome of the diverticulum. [ 8 ] Colonic diverticular bleeding ceases spontaneously in 70% to 90% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, re-bleeding was observed during conservative treatment in 16%-38% of the patients with diverticular bleeding [7], and in particular, it has been reported that the rate of re-bleeding is high at 66% in patients with SRH [21]. The rate of re-bleeding is believed to be higher in patients who are men, older (>70 years), severely anemic (hemoglobin levels <8 g/dL), use antithrombotic agents, have a history of hypertension and hyperlipidemia, have a high body mass index, have poor ability to perform activities of daily living [22], present with tachycardia at the time of the consultation, have the bleeding diverticulum located in the ascending colon, and who have a long hospital stay [22][23][24][25][26]. The present results regarding the characteristics of patients with a high rate of spontaneous hemostasis following conservative treatment are in agreement with the previously reported characteristics of patients with rebleeding.…”
Section: Plos Onementioning
confidence: 99%